Escape from Hangtown [large type] - Sweazy, Larry D. (Wheeler Publishing Large Print, 2015)
"Lucas Fume has been exonerated of the murder charge that put him in prison seven years ago. But he isn't free yet. Not while his friend, former slave Zeke Henry, remains a fugitive wrongly accused of assaulting Senator Barlow's daughter, Celia. Lucas wouldn't have his freedom or wealth--let alone his life--if it weren't for Zeke. And he knows that the only way to clear his friend's name is to prove the identity of Celia's true attacker: Senator Barlow himself. Now Lucas has a plan to take on the powerful Senator--and his son John, aka Lanford Grips--once and for all. The only question is whether it will lead to freedom or the end of a noose" --